2020
DOI: 10.1245/s10434-020-08379-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Factors Affecting Quality of Life After Cytoreductive Surgery with Hyperthermic Intraperitoneal Chemotherapy

Abstract: Background. Previous studies have shown that, overall, quality of life (QoL) decreases within the first 3-6 months after cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS ? HIPEC), returning to baseline levels by 6-12 months. This systematic review aims to evaluate the factors affecting QoL after CRS ? HIPEC within 12 months of surgery. Methods. Electronic databases were investigated searching for articles reporting QoL with validated questionnaires up to September 2019. Risk of bias wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Predicting resectability with preoperative imaging remains an issue [21] and the need to resect multiple organs or digestive segments [22] is particularly di cult to anticipate. Furthermore, extensive disease [23,24], prolonged operative time and postoperative complications are all factors associated with long-term impairment of quality of life [10], which has to be considered when performing CRS and HIPEC for such patients. Since the only therapeutic alternatives are debulking and systemic chemotherapy, which are both palliative options [25], CRS and HIPEC in this population may be considered in a curative intent, but only if a complete CRS is achievable with acceptable postoperative morbidity and impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predicting resectability with preoperative imaging remains an issue [21] and the need to resect multiple organs or digestive segments [22] is particularly di cult to anticipate. Furthermore, extensive disease [23,24], prolonged operative time and postoperative complications are all factors associated with long-term impairment of quality of life [10], which has to be considered when performing CRS and HIPEC for such patients. Since the only therapeutic alternatives are debulking and systemic chemotherapy, which are both palliative options [25], CRS and HIPEC in this population may be considered in a curative intent, but only if a complete CRS is achievable with acceptable postoperative morbidity and impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The peritoneal cancer index (PCI) [8] is a quantitative measure that describes the extent of peritoneal disease at surgery. A very high PCI may be considered as a contraindication for CRS, as it signi cantly increases the morbidity and mortality associated with the procedure [9], along with a signi cant impact on quality of life [10]. While CRS and HIPEC have improved oncological outcomes for patients with PMP, this procedure is associated with high operative mortality (0-18%) and morbidity (33-56%) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 14 participants who underwent the CRS-HIPEC procedure, four were unable to attend a follow up appointment due to not being well enough (n = 2), living too far away (n = 1), and university closure/restrictions during the COVID-19 pandemic (n = 1). The median (IQR) number of weeks between CRS-HIPEC and follow-up assessment was 13 (12)(13)(14).…”
Section: Post-operativementioning
confidence: 99%
“…For the specific determinants, we noted that QoL was negatively influenced by higher age, female sex, prolonged operation time, extensive disease (high PCI), residual disease, adjuvant chemotherapy, postoperative complications, stoma placement, and recurrent disease. 5…”
Section: Presentmentioning
confidence: 99%
“…Secondary outcomes were QoL and reported symptoms over time. 5 We included 14 studies that used 12 different questionnaires, and reported data were collected for 1556 patients (dropout < 50% in 4 studies). Overall, collected data showed indeed a diminished QoL within 3 months after surgery but with a recovery to baseline by 12 months.…”
Section: Presentmentioning
confidence: 99%